2014
DOI: 10.1007/s10753-014-9947-5
|View full text |Cite
|
Sign up to set email alerts
|

Protein Malnutrition Alters Spleen Cell Proliferation and IL-2 and IL-10 Production by Affecting the STAT-1 and STAT-3 Balance

Abstract: Protein malnutrition (PM) is an important public health problem that affects resistance to infection by impairing a number of physiological processes. PM induces structural changes in the lymphoid organs that affect the roles of the immune and inflammatory responses in a crucial way. The activation of different transcription factors, including signal transducer and activator of transcription (STAT) family members, leads to the production of different cytokines, which are mediators essential to mounting adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 44 publications
(61 reference statements)
3
26
0
4
Order By: Relevance
“…7,10 An important finding of the present study was the marked reduction in the spontaneous production of IL-2 in inoculated malnourished mice (G1) compared to the other groups, suggesting a deficient Th1 immune response during malnutrition in conjunction with infection. Separate analysis of malnutrition revealed no difference in the spontaneous production of IL-2 between malnourished (G2) and nourished (G4) animals, in agreement with Mello et al [44].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…7,10 An important finding of the present study was the marked reduction in the spontaneous production of IL-2 in inoculated malnourished mice (G1) compared to the other groups, suggesting a deficient Th1 immune response during malnutrition in conjunction with infection. Separate analysis of malnutrition revealed no difference in the spontaneous production of IL-2 between malnourished (G2) and nourished (G4) animals, in agreement with Mello et al [44].…”
Section: Discussionsupporting
confidence: 91%
“…Separate analysis of malnutrition revealed no difference in the spontaneous production of IL‐2 between malnourished (G2) and nourished (G4) animals, in agreement with Mello et al . .…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the underlying mechanisms by which L3G promotes the expression of pro-inflammatory cytokines. We found that STAT1, which is a transcription factor that regulates the expression of interferons and interleukins, [50][51][52] was involved in the L3Gpromoted cytokine upregulation ( Figure 4). As discussed above, the interaction between Tim-3 and Gal-9 is a negative interaction.…”
Section: Discussionmentioning
confidence: 96%
“…Além disso, a desnutrição pode ocasionar alterações psico-motoras, alterações morfológicas e funcionais em diversos órgãos: baço (MELLO et al,2014) pulmões (LIU et al,2014), fígado (GIUSTO et al,2014,alterações no sistema imunológico (MELLO et al,2014) e na matriz extracelular (MEC) (BORELLI et al, 2009). Alterações hematológicas e na MEC pode contribuir para a hipoplasia observada na medula óssea em camundongos desnutridos.…”
Section: Morte Celular Na Tg2-\-unclassified